2014
DOI: 10.1210/jc.2014-1783
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Structure and Function in Cushing's Syndrome: A Cardiac Magnetic Resonance Imaging Study

Abstract: Background:Patients with Cushing's syndrome have left ventricular (LV) hypertrophy and dysfunction on echocardiography, but echo-based measurements may have limited accuracy in obese patients. No data are available on right ventricular (RV) and left atrial (LA) size and function in these patients.Objectives:The objective of the study was to evaluate LV, RV, and LA structure and function in patients with Cushing's syndrome by means of cardiac magnetic resonance, currently the reference modality in assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
77
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 37 publications
(69 reference statements)
2
77
0
3
Order By: Relevance
“…Overall, this study adds to the scenario that the observed heart abnormalities in patients with CS are not directly related to blood pressure, and other contributing factors have to be considered. In this line, the reversibility of the structural changes did not relate to changes in blood pressure after treatment in two studies [8,9] and, also, hypertension does not seem to be an independent risk factor for long-term mortality in Cushing's disease [4].…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…Overall, this study adds to the scenario that the observed heart abnormalities in patients with CS are not directly related to blood pressure, and other contributing factors have to be considered. In this line, the reversibility of the structural changes did not relate to changes in blood pressure after treatment in two studies [8,9] and, also, hypertension does not seem to be an independent risk factor for long-term mortality in Cushing's disease [4].…”
mentioning
confidence: 86%
“…LV mass index, however, is likely to be overestimated in echo-based studies. In a study that applied cardiac magnetic resonance (CMR) [9], subclinical biventricular and left atrium (LA) systolic dysfunction, as well as mainly regional LV wall thickness were found, although clinical LV hypertrophy according to the CMR criteria was detected in only one of the 18 patients. One study using ECG detected subtle abnormalities, LV hypertrophy and prolonged QT-corrected dispersion [10].…”
mentioning
confidence: 99%
See 3 more Smart Citations